+0

# CPhill's Challenge

+6
451
6
+78755

Here's an old one that I ran across the other day.....I still think it's a nice problem.....

As seen below, a line is tangent to the parabola y = x^2 at  C

At the same time, a line with the same slope cuts the parabola at AB

Your mission, should you decide to accept it, is to prove that the area ADCBA [ the area between the segment AB and the "bottom"  part of the parabola ] is 4/3 that of the area of triangle ABC.........Good Luck....!!!!

CPhill  Oct 29, 2015

#3
+18715
+35

Here's an old one that I ran across the other day.....I still think it's a nice problem.....

As seen below, a line is tangent to the parabola y = x^2 at  C

At the same time, a line with the same slope cuts the parabola at AB

Your mission, should you decide to accept it, is to prove that the area ADCBA [ the area between the segment AB and the "bottom"  part of the parabola ] is 4/3 that of the area of triangle ABC.........Good Luck....!!!!

We have:

$$\boxed{~ \text{parabola}: \quad y = x^2 \qquad y' = 2x \\ \text{line } \overline{AB} : \quad y = m\cdot x +b\\ \vec{A} = \dbinom{x_a}{y_a} = \dbinom{x_a}{x_a^2}\\ \vec{B} = \dbinom{x_b}{y_b} = \dbinom{x_b}{x_b^2}\\ \vec{C} = \dbinom{x_c}{y_c} = \dbinom{x_c}{x_c^2} ~}$$

1. Area of triangle ABC

$$\begin{array}{rcl} 2A_{\text{triangle}} = 2A_t &=& | (\vec{C} - \vec{A})\times (\vec{B} - \vec{A})|\\ &=& \left| \dbinom{x_c-x_a}{x_c^2-x_a^2} \times \dbinom{x_b-x_a}{x_b^2-x_a^2} \right| \\ &=&(x_c-x_a)(x_b^2-x_a^2)-(x_c^2-x_a^2)(x_b-x_a)\\ &=&(x_c-x_a)(x_b-x_a)(x_b+x_a)-(x_c-x_a)(x_c+x_a)(x_b-x_a)\\ &=&(x_c-x_a)(x_b-x_a)[(x_b+x_a)-(x_c+x_a)]\\ &=&(x_c-x_a)(x_b-x_a)(x_b+x_a-x_c-x_a)\\ \mathbf{2A_t}& \mathbf{=}&\mathbf{(x_c-x_a)(x_b-x_a)(x_b-x_c)}\\ \end{array}$$

$$\begin{array}{rcl} \text{slope of the line } \overline{AB}: \quad 2x_c = m &=&\frac{y_b-y_a}{x_b-x_a}\\ &=&\frac{x_b^2-x_a^2}{x_b-x_a}\\ &=&\frac{(x_b-x_a)(x_b+x_a)}{x_b-x_a}\\ &=&x_b+x_a\\ 2x_c = m &=&x_b+x_a\\ 2x_c &=& x_b+x_a\\ \boxed{~x_c = \frac{x_b+x_a}{2} ~} \end{array}\\\\ \begin{array}{rcl} \\ x_c-x_a &=& \frac{x_b+x_a}{2}-x_a = \frac{x_b-x_a}{2}\\ x_b-x_c &=& x_b - \frac{x_b+x_a}{2} = \frac{x_b-x_a}{2}\\\\ 2A_t& =& (x_c-x_a)(x_b-x_a)(x_b-x_c) \qquad |\qquad x_c-x_a = x_b-x_c = \frac{x_b-x_a}{2}\\ 2A_t& =& (\frac{x_b-x_a}{2})(x_b-x_a)(\frac{x_b-x_a}{2} )\\ 2A_t& =& \frac{1}{4}\cdot (x_b-x_a)^3\\ \boxed{~ A_t = \frac{1}{8}\cdot (x_b-x_a)^3 ~} \end{array}$$

$$\begin{array}{rcl} A_{\text{parabola}} = A_p &=& \int \limits_{x_a}^{x_b} { (mx+b)\ dx} - \int \limits_{x_a}^{x_b} { x^2\ dx}\\ &=& m\int \limits_{x_a}^{x_b} { x\ dx} + b\int \limits_{x_a}^{x_b} { dx} - \int \limits_{x_a}^{x_b} { x^2\ dx}\\ &=& \frac{m}{2}[x^2]_{x_a}^{x_b} + b[x]_{x_a}^{x_b} - \frac{1}{3}[x^3]_{x_a}^{x_b}\\ \mathbf{A_p} & \mathbf{=} & \mathbf{ \frac{m}{2}(x_b^2-x_a^2) + b(x_b-x_a) - \frac{1}{3}(x_b^3-x_a^3) }\\\\ && \boxed{~ \begin{array}{rcl} (a-b)^3 &=& a^3-3a^2b+3ab^2-b^3\\ a^3-b^3&=&(a-b)^3+3ab(a-b)\\ a^3-b^3&=&(a-b)[(a-b)^2+3ab]\\ a^3-b^3&=&(a-b)[a^2-2ab+b^2+3ab]\\ a^3-b^3&=&(a-b)[a^2+ab+b^2]\\ \end{array} ~}\\\\ && x_b^3-x_a^3 = (x_b-x_a)(x_b^2+x_bx_a+x_a^2)\\\\ A_p & = & \frac{m}{2}(x_b-x_a)(x_b+x_a) + b(x_b-x_a) - \frac{1}{3}(x_b-x_a)(x_b^2+x_bx_a+x_a^2) \\ A_p & = & (x_b-x_a)[\frac{m}{2}(x_b+x_a) + b - \frac{1}{3}(x_b^2+x_bx_a+x_a^2) ] \\\\ && \text{line }: \quad y=mx+b \qquad m=\ ? \qquad b=\ ? \\ && \boxed{~ \begin{array}{rcl} \frac{ y-y_a } { x - x_a } &=& \frac{ y_b-y_a } { x_b - x_a }\\ y-y_a &=& (x - x_a) \frac{ y_b-y_a } { x_b - x_a }\\ y &=& (x - x_a) \frac{ y_b-y_a } { x_b - x_a } +y_a \quad y_b = x_b^2 \quad y_a = x_a^2\\ y &=& (x - x_a) \frac{ x_b^2-x_a^2 } { x_b - x_a } +x_a^2\\ y &=& (x - x_a) \frac{ (x_b-x_a)(x_b+x_a) } { x_b - x_a } +x_a^2\\ y &=& (x - x_a)(x_b+x_a) +x_a^2\\ y &=& x(x_b+x_a) - x_a(x_b+x_a) +x_a^2\\ y &=& x(x_b+x_a) - x_ax_b-x_a^2 +x_a^2\\ y &=& x\underbrace{(x_b+x_a)}_{=m} \ \underbrace{- x_ax_b}_{=b}\\ \end{array} ~}\\\\ \mathbf{m}&\mathbf{=}& \mathbf{x_b+x_a}\\ \mathbf{b}&\mathbf{=}& \mathbf{-x_ax_b}\\\\ A_p & = & (x_b-x_a)[\frac{x_b+x_a}{2}(x_b+x_a) -x_ax_b - \frac{1}{3}(x_b^2+x_bx_a+x_a^2) ] \quad |\quad \cdot \frac66\\ A_p & = & \frac16(x_b-x_a)[3(x_b+x_a)^2 -6x_ax_b - 2(x_b^2+x_bx_a+x_a^2) ] \\ A_p & = & \frac16(x_b-x_a)(3x_b^2+6x_bx_a+3x_a^2 -6x_ax_b - 2x_b^2-2x_bx_a-2x_a^2) \\ A_p & = & \frac16(x_b-x_a)(x_b^2 -2x_bx_a+ x_a^2) \\ A_p & = & \frac16(x_b-x_a)(x_b-x_a)^2 \\ \boxed{~ A_p = \frac16(x_b-x_a)^3 ~}\\ \end{array}$$

3. Ratio $$\frac{A_t}{A_p}$$

$$\begin{array}{rcl} \frac{A_t}{A_p} &=& \frac { \frac{1}{8}\cdot (x_b-x_a)^3 } { \frac16(x_b-x_a)^3 }\\ \frac{A_t}{A_p} &=& \frac{1}{8}\cdot \frac61 \\ \frac{A_t}{A_p} &=& \frac{6}{8} \\ \mathbf{\dfrac{A_t}{A_p}} &\mathbf{=} & \mathbf{\dfrac{3}{4} }\\ \end{array}$$

heureka  Oct 30, 2015
Sort:

#2
+91053
0

http://web2.0calc.com/questions/the-solution-way-with-an-example/new#edit

(not general so Chris did not accept it     )

I liked it!

Melody  Oct 30, 2015
#3
+18715
+35

Here's an old one that I ran across the other day.....I still think it's a nice problem.....

As seen below, a line is tangent to the parabola y = x^2 at  C

At the same time, a line with the same slope cuts the parabola at AB

Your mission, should you decide to accept it, is to prove that the area ADCBA [ the area between the segment AB and the "bottom"  part of the parabola ] is 4/3 that of the area of triangle ABC.........Good Luck....!!!!

We have:

$$\boxed{~ \text{parabola}: \quad y = x^2 \qquad y' = 2x \\ \text{line } \overline{AB} : \quad y = m\cdot x +b\\ \vec{A} = \dbinom{x_a}{y_a} = \dbinom{x_a}{x_a^2}\\ \vec{B} = \dbinom{x_b}{y_b} = \dbinom{x_b}{x_b^2}\\ \vec{C} = \dbinom{x_c}{y_c} = \dbinom{x_c}{x_c^2} ~}$$

1. Area of triangle ABC

$$\begin{array}{rcl} 2A_{\text{triangle}} = 2A_t &=& | (\vec{C} - \vec{A})\times (\vec{B} - \vec{A})|\\ &=& \left| \dbinom{x_c-x_a}{x_c^2-x_a^2} \times \dbinom{x_b-x_a}{x_b^2-x_a^2} \right| \\ &=&(x_c-x_a)(x_b^2-x_a^2)-(x_c^2-x_a^2)(x_b-x_a)\\ &=&(x_c-x_a)(x_b-x_a)(x_b+x_a)-(x_c-x_a)(x_c+x_a)(x_b-x_a)\\ &=&(x_c-x_a)(x_b-x_a)[(x_b+x_a)-(x_c+x_a)]\\ &=&(x_c-x_a)(x_b-x_a)(x_b+x_a-x_c-x_a)\\ \mathbf{2A_t}& \mathbf{=}&\mathbf{(x_c-x_a)(x_b-x_a)(x_b-x_c)}\\ \end{array}$$

$$\begin{array}{rcl} \text{slope of the line } \overline{AB}: \quad 2x_c = m &=&\frac{y_b-y_a}{x_b-x_a}\\ &=&\frac{x_b^2-x_a^2}{x_b-x_a}\\ &=&\frac{(x_b-x_a)(x_b+x_a)}{x_b-x_a}\\ &=&x_b+x_a\\ 2x_c = m &=&x_b+x_a\\ 2x_c &=& x_b+x_a\\ \boxed{~x_c = \frac{x_b+x_a}{2} ~} \end{array}\\\\ \begin{array}{rcl} \\ x_c-x_a &=& \frac{x_b+x_a}{2}-x_a = \frac{x_b-x_a}{2}\\ x_b-x_c &=& x_b - \frac{x_b+x_a}{2} = \frac{x_b-x_a}{2}\\\\ 2A_t& =& (x_c-x_a)(x_b-x_a)(x_b-x_c) \qquad |\qquad x_c-x_a = x_b-x_c = \frac{x_b-x_a}{2}\\ 2A_t& =& (\frac{x_b-x_a}{2})(x_b-x_a)(\frac{x_b-x_a}{2} )\\ 2A_t& =& \frac{1}{4}\cdot (x_b-x_a)^3\\ \boxed{~ A_t = \frac{1}{8}\cdot (x_b-x_a)^3 ~} \end{array}$$

$$\begin{array}{rcl} A_{\text{parabola}} = A_p &=& \int \limits_{x_a}^{x_b} { (mx+b)\ dx} - \int \limits_{x_a}^{x_b} { x^2\ dx}\\ &=& m\int \limits_{x_a}^{x_b} { x\ dx} + b\int \limits_{x_a}^{x_b} { dx} - \int \limits_{x_a}^{x_b} { x^2\ dx}\\ &=& \frac{m}{2}[x^2]_{x_a}^{x_b} + b[x]_{x_a}^{x_b} - \frac{1}{3}[x^3]_{x_a}^{x_b}\\ \mathbf{A_p} & \mathbf{=} & \mathbf{ \frac{m}{2}(x_b^2-x_a^2) + b(x_b-x_a) - \frac{1}{3}(x_b^3-x_a^3) }\\\\ && \boxed{~ \begin{array}{rcl} (a-b)^3 &=& a^3-3a^2b+3ab^2-b^3\\ a^3-b^3&=&(a-b)^3+3ab(a-b)\\ a^3-b^3&=&(a-b)[(a-b)^2+3ab]\\ a^3-b^3&=&(a-b)[a^2-2ab+b^2+3ab]\\ a^3-b^3&=&(a-b)[a^2+ab+b^2]\\ \end{array} ~}\\\\ && x_b^3-x_a^3 = (x_b-x_a)(x_b^2+x_bx_a+x_a^2)\\\\ A_p & = & \frac{m}{2}(x_b-x_a)(x_b+x_a) + b(x_b-x_a) - \frac{1}{3}(x_b-x_a)(x_b^2+x_bx_a+x_a^2) \\ A_p & = & (x_b-x_a)[\frac{m}{2}(x_b+x_a) + b - \frac{1}{3}(x_b^2+x_bx_a+x_a^2) ] \\\\ && \text{line }: \quad y=mx+b \qquad m=\ ? \qquad b=\ ? \\ && \boxed{~ \begin{array}{rcl} \frac{ y-y_a } { x - x_a } &=& \frac{ y_b-y_a } { x_b - x_a }\\ y-y_a &=& (x - x_a) \frac{ y_b-y_a } { x_b - x_a }\\ y &=& (x - x_a) \frac{ y_b-y_a } { x_b - x_a } +y_a \quad y_b = x_b^2 \quad y_a = x_a^2\\ y &=& (x - x_a) \frac{ x_b^2-x_a^2 } { x_b - x_a } +x_a^2\\ y &=& (x - x_a) \frac{ (x_b-x_a)(x_b+x_a) } { x_b - x_a } +x_a^2\\ y &=& (x - x_a)(x_b+x_a) +x_a^2\\ y &=& x(x_b+x_a) - x_a(x_b+x_a) +x_a^2\\ y &=& x(x_b+x_a) - x_ax_b-x_a^2 +x_a^2\\ y &=& x\underbrace{(x_b+x_a)}_{=m} \ \underbrace{- x_ax_b}_{=b}\\ \end{array} ~}\\\\ \mathbf{m}&\mathbf{=}& \mathbf{x_b+x_a}\\ \mathbf{b}&\mathbf{=}& \mathbf{-x_ax_b}\\\\ A_p & = & (x_b-x_a)[\frac{x_b+x_a}{2}(x_b+x_a) -x_ax_b - \frac{1}{3}(x_b^2+x_bx_a+x_a^2) ] \quad |\quad \cdot \frac66\\ A_p & = & \frac16(x_b-x_a)[3(x_b+x_a)^2 -6x_ax_b - 2(x_b^2+x_bx_a+x_a^2) ] \\ A_p & = & \frac16(x_b-x_a)(3x_b^2+6x_bx_a+3x_a^2 -6x_ax_b - 2x_b^2-2x_bx_a-2x_a^2) \\ A_p & = & \frac16(x_b-x_a)(x_b^2 -2x_bx_a+ x_a^2) \\ A_p & = & \frac16(x_b-x_a)(x_b-x_a)^2 \\ \boxed{~ A_p = \frac16(x_b-x_a)^3 ~}\\ \end{array}$$

3. Ratio $$\frac{A_t}{A_p}$$

$$\begin{array}{rcl} \frac{A_t}{A_p} &=& \frac { \frac{1}{8}\cdot (x_b-x_a)^3 } { \frac16(x_b-x_a)^3 }\\ \frac{A_t}{A_p} &=& \frac{1}{8}\cdot \frac61 \\ \frac{A_t}{A_p} &=& \frac{6}{8} \\ \mathbf{\dfrac{A_t}{A_p}} &\mathbf{=} & \mathbf{\dfrac{3}{4} }\\ \end{array}$$

heureka  Oct 30, 2015
#4
+91053
+7

Great work Heureks

Melody  Oct 30, 2015
#5
+26329
+7

Very nicely done heureka!

Alan  Oct 30, 2015
#6
+78755
+5

Very nice, heureka...I re-worked this one the other day....I did something similar with the integration part, but, for the area of the triangle, I found the length of the base and then used the "formula" for finding the distance from a point not on a line [in this case, C]  to the line segment AB to find the altitude of the triangle......

There are probably several other methods to solving this.......I actually found it in a different way a long time ago, but, now........I don't remember exactly what I did.....LOL!!!!!

Good job....!!!....5 points from me.....!!!!

CPhill  Oct 30, 2015
edited by CPhill  Oct 30, 2015

### 4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details